Carcinoid tumor of the gallbladder - Machado, Marcel Cerqueira Cesar (1998)
The carcinoid tumor is a relatively rare type of endocrine tumor, which arises mainly in the gastrointestinal tract. Primary gallbladder and biliary duct system carcinoids comprise less than 1% of all carcinoid tumors arising from any tissue or organ in the body. We describe a case of carcinoid tumor of the gallbladder in a 39-year-old man. There have been only 32 cases described in the literature.